Improving cassava growth and yield through auxin paste treatment on cuttings: A clonal comparison - Naufal Dani Fauzan; Yusnita Yusnita; Sandi Asmara; Agus Karyanto; R. A. Diana Widyastuti (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2025)
Cassava is an important crop for carbohydrate production, primarily propagated through stem cuttings. Auxin has been proven for decades to be an effective material for increasing the rooting of cuttings. The combination of NAA and IBA is more effective than a single auxin and synergizes in promoting root growth. This study aimed to evaluate the growth and yield of cassava clones to different auxin concentrations of NAA+IBA mixture. The research used a randomized complete block design arranged in a factorial with 9 (3x3) treatments repeated 3 times. The first factor was the type of cassava clone, consisting of K1 = Garuda, K2 = Katsesart, and K3 = Roti, while the second factor was the concentration of NAA + IBA (1:1), namely A0 (0 ppm), A1 (1,000 ppm), and A2 (2,000 ppm). The results showed that clones responded differently to auxin concentration. Increasing the auxin concentration from 1,000 ppm to 2,000 ppm did not increase growth and yield, irrespective of clones. The application NAA + IBA (1:1) significantly increased fresh leaf weight, plant height, fresh stem weight, total number of roots, and number of storage roots as compared to the control at 8 months after planting (MAP). At 8 MAP, the Kasetsart clone produced higher growth and yield than Garuda and Roti clones, as indicated by the average plant height, total number of roots, and number of storage roots. Keywords: hormone; IBA; Manihot esculenta; NAA; production